Response of subterranean hypocotyl region of seedlings in screening muskmelon (Cucumis melo) for resistance to Fusarium oxysporum f.sp melonis - THOMAS, PIOUS; MORE, TUKARAM A; SEN, BINEETA (The Indian Journal of Agricultural Sciences, 2013)
Three methods of artificial screening, viz seed-coat puncturing and inoculation, seed and radicle inoculation, and sand infestation, were attempted for resistance to Fusarium oxysporum Schlecht. f. sp melonis Snyder & Hansen, using 14 genotypes of melons (Cucumis spp) in comparison with screening in fields. Seed-coat puncturing and inoculation by soaking in spore Suspension proved the best, permitting theclassification of genotypes into distinct resistant categories in 28 qays. Many apparently healthy surviving seedlings when uprooted showed different degrees of damage in the subterranean hypocotyl region. Consideration of this factor helped exclude the chance of classifying any apparently healthy plants as resistant to the pathogen. 'Chittidar' muskmelon (C. melo L.) and 'IC 540' long melon (C. mefo L. var utilissimus Duth. & Full.) showed high resistance in field as well as artificial screening.